GIS-material for the archaeological project: Burial and settlement area in Hästholmen - Archaeology department, Östergötland County Museum (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
By request of Ödeshög municipality, the County Museum of Östergötland performed a field evaluation of the property Hästholmen 7:1, during August and September 2009. The evaluation took place within the burial and settlement area RAÄ 236. Approx. 270 features were discovered, consisting of graves, cultural layers and settlement features, of which five cremation graves, one inhumation grave and approx. 70 settlement features were excavated. Finds of pottery and iron and stone objects and were collected. There are two chronological phases, with the settlement remains dating to the Early bronze Age, and the graves dating to the Early Iron Age and the transition between the Pre-Roman and the Roman Iron Age.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the field evaluation was to describe the character, dating and extent of the archaeological remains, and to investigate the connection to other known ancient monuments in the vicinity. The result will be used as a basis for future decisions regarding the remnants by the County Administrative Board, and serve as guidance for the developer's planning.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På uppdrag av Ödeshögs kommun utförde Östergötlands länsmuseum en arkeologisk förundersökning inom Hästholmen 7:1 under augusti och september 2009. Den arkeologiska förundersökningen utfördes inom RAÄ 236, ett grav- och boplatsområde. Det framkom ca 270 anläggningar i form av gravar, kulturlager och boplatsanläggningar. Fem brandgravar, en skelettgrav och ca 70 boplatsanläggningar undersöktes. Fynd av bland annat keramik, järnföremål och stenmaterial togs tillvara. Dateringarna visar på två olika kronologiska faser där boplatsanläggningarna daterats till äldre bronsålder (period II och III) medan gravarna härrör från äldre järnålder och skiftet mellan förromersk och romersk järnålder.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen var att undersöka fornlämningarnas karaktär, datering och utbredning. I målsättningen ingick också att finna samband med de redan kända fornlämningarna i närområdet. Resultatet av förundersökningen skall utgöra beslutsunderlag för länsstyrelsens fortsatta hantering av ärendet samt utgöra ett underlag för uppdragsgivarens planeringsarbete.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Grav- och boplatsområde i Hästholmen
Keywords: Early Iron Age; äldre järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi